A Study of the Abundance of Some Adult Culicine Mosquitoes in Ten Villages of Chitwan District, Nepal - Neupane, Vaijayanti Devi; Gautam, Ishan; Tamrakar, A. S.; Shrestha, Shambhu Raj (Journal of Natural History Museum, 2009)
A study was carried out at 10 villages of Chitwan District of Nepal during August-September, 1997 to March- April, 1998. A total of 12 species among 1197 samples were collected. Culex quinquefasciatus, Cx. fuscocephala, Cx. tritaeniorhynchus, Cx. gelidus, Cx. thelieri were previously reported, vector of different mosquito born diseases were recorded. Cx. quinquefasciatus was the most abundant both in post monsoon (26.90%) and pre monsoon (18.7%). Highest resting density (Human) of 9.33 was recorded in Post Monsoon at 25.75º C in Champanagar. Indoor resting density (Cattle) was highest in Suryapur at 22º C in Post Monsoon. The highest outdoor density (0.22) was at 22.5º C in Kholesimal in Pre Monsoon. Resting habit of Cx. tritaeniorhynchus & Cx. mimulus was infinitive in Post Monsoon.  Key Words:  Culex; JE Filariasis;  Abundant;  Resting habit; Chitwan. Journal of Natural History Museum Vol. 24, 2009,Page: 103-113